2021
DOI: 10.1002/cad.20433
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and severity of teen dating violence victimization in community and at‐risk adolescents in Spain

Abstract: The aim of the present study was to determine the prevalence and severity of teen dating violence victimization in Spanish adolescents from both community and at‐risk samples. The sample comprised 1,105 community adolescents from secondary schools, 149 adolescents from child, and adolescent mental health centers, 129 from residential care centers associated with the child welfare system, and 101 from centers in the juvenile justice system. The participants, aged between 14 and 17 years, were interviewed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
2
6
1
2
Order By: Relevance
“…It comprises five new primary studies and a systematic review of 25 studies that reported prevalence estimates in Europe. The results found in these studies corroborate patterns of gender differences found previously: Among heterosexual romantic partners, sexual violence is far more likely to be perpetrated by males, irrespective of the informant (Oyarzún et al., 2021; Tomaszewska & Schuster, 2021). In contrast, prevalence estimates based on self‐reported physical violence perpetration tend to show higher rates for female than for male adolescents (Baier et al., 2021; Bertok et al., 2021; Tomaszewska & Schuster, 2021; Toplu‐Demirtaş & Aracı‐İyiaydın, 2021).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…It comprises five new primary studies and a systematic review of 25 studies that reported prevalence estimates in Europe. The results found in these studies corroborate patterns of gender differences found previously: Among heterosexual romantic partners, sexual violence is far more likely to be perpetrated by males, irrespective of the informant (Oyarzún et al., 2021; Tomaszewska & Schuster, 2021). In contrast, prevalence estimates based on self‐reported physical violence perpetration tend to show higher rates for female than for male adolescents (Baier et al., 2021; Bertok et al., 2021; Tomaszewska & Schuster, 2021; Toplu‐Demirtaş & Aracı‐İyiaydın, 2021).…”
Section: Introductionsupporting
confidence: 89%
“…In Spain, Fernández‐González et al. (2014) showed that females aged 18–20 years were four times more likely to experience injury due to physical dating aggression (also see Oyarzún et al., 2021). These findings are consistent with the limited evidence from hospital data, which shows that female adolescents are far more likely to visit emergency departments for injuries due to intimate partner violence (Epstein‐Ngo et al., 2013; Ranney & Mello, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The second contribution, a study by Oyarzún et al. (2021), examines the prevalence rates and severity of different forms of TDV victimization in a community sample of Spanish adolescents and several at‐risk samples, such as from child and adolescent mental health centers, residential care centers associated with the child welfare system, and centers in the juvenile justice system. The authors discuss the relevance of preventing adolescents from experiencing violence in their close relationships, especially in at‐risk adolescents.…”
Section: Contributionsmentioning
confidence: 99%